Evolution of Reproductive Division of Labor – Lessons Learned From the Social Amoeba Dictyostelium discoideum During Its Multicellular Development - Dhakshinamoorthy, Ranjani; Singh, Shashi P. (Frontiers in Cell and Developmental Biology, 2021)
The origin of multicellular life from unicellular beings is an epochal step in the evolution of eukaryotes. There are several factors influencing cell fate choices during differentiation and morphogenesis of an organism. Genetic make-up of two cells that unite and fertilize is the key factor to signal the formation of various cell-types in due course of development. Although ploidy of the cell-types determines the genetics of an individual, the role of ploidy in cell fate decisions remains unclear. Dictyostelium serves as a versatile model to study the emergence of multicellular life from unicellular life forms. In this work, we investigate the role played by ploidy status of a cell on cell fate commitments during Dictyostelium development. To answer this question, we created Dictyostelium cells of different ploidy: haploid parents and derived isogenic diploids, allowing them to undergo development. The diploid strains used in this study were generated using parasexual genetics. The ploidy status of the haploids and diploids were confirmed by microscopy, flow cytometry, and karyotyping. Prior to reconstitution, we labeled the cells by two methods. First, intragenic expression of red fluorescent protein (RFP) and second, staining the amoebae with a vital, fluorescent dye carboxyfluorescein succinimidyl ester (CFSE). RFP labeled haploid cells allowed us to track the haploids in the chimeric aggregates, slugs, and fruiting bodies. The CFSE labeling method allowed us to track both the haploids and the diploids in the chimeric developmental structures. Our findings illustrate that the haploids demonstrate sturdy cell fate commitment starting from the aggregation stage. The haploids remain crowded at the aggregation centers of the haploid–diploid chimeric aggregates. At the slug stage haploids are predominantly occupying the slug posterior, and are visible in the spore population in the fruiting bodies. Our findings show that cell fate decisions during D. discoideum development are highly influenced by the ploidy status of a cell, adding a new aspect to already known factors Here, we report that ploidy status of a cell could also play a crucial role in regulating the cell fate commitments.